2016
DOI: 10.1002/ana.24728
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation and climbing fiber synaptic pathology in essential tremor

Abstract: Essential tremor (ET) patients have abnormal climbing fiber (CF) synapses in the parallel fiber territory in the cerebellum, and these abnormal CF synapses are inversely correlated with tremor severity. We therefore examined CF synaptic pathology in ET cases with and without thalamic DBS and assessed the association with tremor severity. We found that CF synaptic pathology was inversely correlated with tremor severity in ET cases without DBS, and this correlation disappeared in ET cases with DBS. Our data sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…In this study, we found that ET cases and controls differ with respect to CF-PC synaptic pathology, confirming results from previous studies [47]. Specifically, ET cases have lower CF synaptic densities and higher percentages of CFs extending into the PF territory compared to controls.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, we found that ET cases and controls differ with respect to CF-PC synaptic pathology, confirming results from previous studies [47]. Specifically, ET cases have lower CF synaptic densities and higher percentages of CFs extending into the PF territory compared to controls.…”
Section: Discussionsupporting
confidence: 91%
“…Clinical and neuroimaging evidence both suggest the importance of the cerebellum in tremor generation in ET [2,3]. In recent studies, we observed climbing fiber-Purkinje cell (CF-PC) synaptic abnormalities in the ET cerebellum; compared to controls, ET cases exhibited decreased CF synaptic density and an increased percentage of CFs extending into the parallel fiber (PF) territory [47]. These changes coexist with a host of other pathological changes in PCs in ET, such as a decrease in PC counts [8] and an increase in torpedoes and associated PC axonal pathologies [8,9], although PC loss is a finding that is variably reproduced [1012].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, we have noted the presence of abnormalities in CF-PC synapses in ET cases: (1) decreased CF-PC synaptic density on proximal PC dendrites, the normal synaptic domain of climbing fibers and (2) abnormal CF-PC synapses in extending into the PF-PC synaptic territory [31]. The number of abnormal distal CF-PC synapses inversely correlated with tremor severity [31, 41] and could be modulated by the deep brain stimulations [28], suggesting a link between this pathological feature and tremor.…”
Section: Introductionmentioning
confidence: 99%
“…In ET they are more concentrated on the distal dendrites and this finding is inversely correlated with tremor severity. Interestingly, this inverse correlation is lost in ET patients treated with DBS confirming the plasticity of these relations . The comparison of ET with PD, spinocerebellar ataxia type 1 and multiple system atrophy patients showed that PD and ET had an increased number of distal climbing fiber terminations whilst multiple system atrophy and spinocerebellar ataxia type 1 patients had fewer climbing fibers terminating in the distal territory .…”
Section: Pathologymentioning
confidence: 73%